Pengaruh Hasil Audit Pelayanan Terhadap Citra Perusahaan Dengan Kepuasan Nasabah Sebagai Variabel Intervening Pada Bank Pembiayaan Rakyat Syariah Puduarta Insani - Muhammad Daffa Baihaqi Purnomo; Nurbaiti Nurbaiti; Nur Ahmadi Bi Rahmadi (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to examine the effect of service audit results on customer satisfaction as an intervening variable on corporate image at BPRS Puduarta Insani Medan. This research is included in the type of quantitative research based on hypothesis testing whose population is BPRS Puduarta Insani customers with a total sample of 60 customers of BPRS Puduarta Insani taken by simple random sampling. This study uses primary data and secondary data as a reference for data obtained from BPRS Puduarta Insani in the form of Audit Results in 2021. The results of the study show that the results of a service audit with customer satisfaction as an intervening variable have a positive and significant effect on corporate image. With r count greater than r table, significant probability < 0.05 and Cronbach results obtained 0.739. So, it can be concluded that customer satisfaction is positively related to company image, which means that if the level of satisfaction increases, the company's image will also be better.